2013
DOI: 10.2298/avb1303125v
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different anesthetic agents on GM-CSF, MCP1, IL1α and TNFα levels in rat sepsis model

Abstract: Anesthetic agents could alter the course and outcome of physical trauma, as well as experimentally or naturally occurring severe infections, by regulating several immune response mechanisms. The aim of our study was to investigate the influence of several commercially used anesthetic agents (ketamine, propofole, pentylentetrazole - PTZ) on cytokine concentrations, animal survival and pathohistological changes in the model of rat sepsis. In adult, male Wistar rats after different anesthetic treatment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This might be explained by the use of higher volume % of sevofl urane that was required for maintenance of surgical anaesthesia in comparison to the LOV group [14]. Respiratory rate increased in dogs from COV group during the withdrawal of the left ligament and thus ketamine was administered to suppress the response to the painful stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by the use of higher volume % of sevofl urane that was required for maintenance of surgical anaesthesia in comparison to the LOV group [14]. Respiratory rate increased in dogs from COV group during the withdrawal of the left ligament and thus ketamine was administered to suppress the response to the painful stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Through the study of granulocyte growth factors they were found to infl uence the fi broblasts and to be able to perform simultaneous indirect stimulation of epithelial cell proliferation accelerated by creating an underlying connective tissue and intercellular substance [19][20][21]. Indirect stimulation was hypothetically expected from G-CSF through the proliferation of fi broblasts, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Also, using a comparative natural-occurrence disease model approach, pathological fi brosis in large animals was suggested to be interesting for further research in human disorder pathogenesis [110]. Many research articles combine different approaches to highlight some pathological phenomenon related to tissue injury and regeneration [111][112][113]. Although the interest to unravel mechanisms of pathological fi brosis in veterinary medicine is evident, and possibilities to fi nd a good model to investigate circulating fi brocytes' nature and function are multiple, these curious cells have not been investigated in large animals, yet.…”
Section: Circulating Fi Brocyte: the Cell In Betweenmentioning
confidence: 99%